A Rare Case of Infected Cervicodorsal Intramedullary Epidermoid Cyst - Chawla, Pawan; Sankhe, Milind (Indian Journal of Neurosurgery, 2020)
Introduction  Intramedullary spinal epidermoid cysts have a reported incidence of less than 1% of intramedullary spinal cord tumors; and out of these, intramedullary epidermoid lesions within the cervical spinal cord are even rarer. Here, we present the case of an adult patient with an infected intramedullary epidermoid cyst, identified on magnetic resonance imaging (MRI) at the C7–D1 level that was successfully excised without any worsening of neurological status.Case Presentation A 23-year-old female patient presented with history of moderate degree intermittent fever followed by gradually progressive right-sided weakness. She had paresthesia below C5 dermatome on the right side. On close inspection of  the back, a tiny sinus opening was noted at the D2 level near the midline. MRI of the spine showed an intramedullary lesion at the C6–D1 level with the tract connecting to the subcutaneous lesion. Somatosensory evoked potential (SSEP) monitoring was done during the surgery with near total excision of the lesion.Conclusion Even though the location is rare, a differential diagnosis of the epidermoid should always be considered. A tiny dermal sinus opening helped us in proper diagnosis, along with surgical excision, by providing us a direct path to the intramedullary lesion. An early diagnosis and treatment with neurophysiological monitoring helped us in the maximum safe resection of the lesion without developing any new deficit.
Keywords: epidermoid; intramedullary; dermoid sinus